Two new species of Monstera (Araceae: Monsteroideae) from the Pacific slope of the Andes in Colombia - Zuluaga, Alejandro; Cedeño-Fonseca, Marco; Mittermeier, Michael (Phytotaxa, 2021)
The genus Monstera is represented in Colombia by 20 species, 12 of them from the Pacific slope of the Andes. Fieldwork between 2017 and 2019 in this region and a thorough revision of the main Colombian herbaria allowed us to discover two undescribed species belonging to Monstera section Monstera. The two new species are described and illustrated using color photographs of vegetative and reproductive features from living material, and compared to Monstera oreophila, M. epipremnoides and M. dissecta from Central America.